Misdiagnosed appendiceal mucinous neoplasms and primary ovarian mucinous tumors present with different pre- and intraoperative characteristics - Yu, Yi; Wang, Tao; Yuan, Zhen; Lin, Wei; Yang, Jiaxin; Cao, Dongyan (Frontiers in Oncology, 2022)
Objective: To identify the differences between the pre- and intraoperative characteristics in misdiagnosed appendiceal mucinous neoplasms (AMNs) and those in primary ovarian mucinous tumors (POMTs) and to establish an effective model for differentiating AMNs from pelvic mucinous tumors. Methods: This study enrolled 70 AMN patients who were misdiagnosed with ovarian tumors and 140 POMT patients who were treated from November 1998 to April 2021 at Peking Union Medical College Hospital. The clinical features and operative findings of the two groups of patients were collected and compared. Results: There were significant differences in age and menopausal status, but no difference in the patients’ clinical manifestations between the two groups. The preoperative serum CA125 and CA199 levels were not different between the two groups. The CEA level (31.04±42.7 vs. 7.11±24.2 ng/ml) was higher in the misdiagnosed AMN group (P < 0.001). The AMNs were smaller than the POMTs that were measured preoperatively by ultrasonography (US) (P<0.05) and measured at surgery (P<0.05). Furthermore, the patients with AMNs more commonly had multinodularity and ascites noted on the preoperative US (P<0.001), on CT (P<0.001), and at surgery (P< 0.001). The two groups also differed in the presence of bilateral disease, in the appendiceal appearance and peritoneal dissemination. Subsequently, a prediction model was developed using multivariable logistic regression, which was evaluated through internal validation. Conclusions: The suspicion of a nongenital organs originated tumor especially origing from appendiceal should be considered in a patient who is older, tumor size less than 12cm, multinodular, presence of mucinous ascites, and elevated serum CEA levels. Bilateral ovarian involvement, peritoneal dissemination, and an abnormal appendiceal appearance found during surgery were the typical features associated with AMNs.